1980
DOI: 10.1126/science.6154315
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Motility by Interferon

Abstract: Interferon derived from human leukocytes, human fibroblasts, and mouse fibroblasts was found to inhibit the motility of cultured cells. It inhibits the tumor-induced motility of capillary endothelial cells as well as the spontaneous migration of other cell types. The ability of a given preparation of interferon to inhibit the motility of a given cell type is proportional to its antiviral activity in that particular cell type. Antiserum to human leukocyte interferon neutralizes both the motility-inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
4

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(108 citation statements)
references
References 16 publications
1
103
0
4
Order By: Relevance
“…These findings support the hypothesis that the antiangiogenic effect of IFN-g on human endothelial cells required other mechanisms besides apoptosis. Human IFN-g inhibits endothelial migration and proliferation (Brouty-Boye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Albini et al, 2000) and has strong antiproliferative effects on NB tumour cells (Ponzoni et al, 1992;Airoldi et al, 2004), from which the human endothelial cells derived. Thus, the antiangiogenic effect was likely due to a combination of apoptosis and reduced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the hypothesis that the antiangiogenic effect of IFN-g on human endothelial cells required other mechanisms besides apoptosis. Human IFN-g inhibits endothelial migration and proliferation (Brouty-Boye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Albini et al, 2000) and has strong antiproliferative effects on NB tumour cells (Ponzoni et al, 1992;Airoldi et al, 2004), from which the human endothelial cells derived. Thus, the antiangiogenic effect was likely due to a combination of apoptosis and reduced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1980, IFN had been shown to inhibit endothelial cell motility [58], and later in the 1980s was shown to inhibit tumor-and allogeneic lymphocyte-induced angiogenesis [59] and to selectively damage the tumor microvascular endothelium, leading to coagulation necrosis of murine tumors selected for resistance to IFN's antiproliferative effects [60]. Further investigations of the angiogenesis inhibitory activities of IFN in the 1990s showed that IFNα could downregulate IL-8 production in fibroblasts [61] and bFGF in human tumor cell lines resistant to IFN's antiproliferative effects [62].…”
Section: Angiogenesis Inhibitionmentioning
confidence: 99%
“…28,29 Moreover, IFN-␣ was the first of the known angiogenesis inhibitors to be evaluated clinically and to show its therapeutic potential in angiogenic diseases, such as childhood hemangioma and Kaposi's sarcoma. 30,31 Its anti-angiogenic activity has been well established by a number of in vitro studies indicating that it can block endothelial cell migration, 8,32 and also downregulate angiogenic factor expression, such as bFGF, IL-8, MMP-2 and MMP-9. [33][34][35][36] IFN-␣ also down-regulates bFGF expression in human carcinomas.…”
Section: Figure 7 Angiostatin Expression In Mcf7 and Mda-mb435 Tumorsmentioning
confidence: 99%
“…5,6 IFN-␣ and IFN-␤ are multifunctional regulatory cytokines involved in the control of cell proliferation and viral infections that also show anti-angiogenic activity both in vitro and in vivo. 7,8 Frequent systemic administration of low-dose IFN-␣ and IFN-␤, or the introduction of their genes in some tumor or stromal cells has produced therapeutic effects against many tumor types in several animal models. [9][10][11] Angiostatic therapy appears to require long-term administration of the inhibitor to ensure tumor growth suppression in vivo.…”
Section: Introductionmentioning
confidence: 99%